Do encontro das águas ao Atlântico negro: organização, difusão de frames e os limites do ativismo transnacional no movimento negro brasileiro - Rosa, Alexandre Reis (2011)
Submitted by Cristiane Oliveira (cristiane.oliveira@fgv.br) on 2011-05-26T15:09:04Z No. of bitstreams: 1 72070100772.pdf: 3082018 bytes, checksum: d9b799ed6e460f338903f6a521cebdef (MD5) === Approved for entry into archive by Suzinei Teles Garcia Garcia(suzinei.garcia@fgv.br) on 2011-05-26T15:10:05Z (GMT) No. of bitstreams: 1 72070100772.pdf: 3082018 bytes, checksum: d9b799ed6e460f338903f6a521cebdef (MD5) === Approved for entry into archive by Suzinei Teles Garcia Garcia(suzinei.garcia@fgv.br) on 2011-05-26T15:10:42Z (GMT) No. of bitstreams: 1 72070100772.pdf: 3082018 bytes, checksum: d9b799ed6e460f338903f6a521cebdef (MD5) === Made available in DSpace on 2011-05-26T17:17:14Z (GMT). No. of bitstreams: 1 72070100772.pdf: 3082018 bytes, checksum: d9b799ed6e460f338903f6a521cebdef (MD5) Previous issue date: 2011-03-02 === My goal in this thesis is to understand the process of transnationalization of Brazilian black movement and its implications for anti-racist struggle in Brazil. In other words, I seek to understand how black Brazilians articulated themselves with the blacks in the world to accomplish their goals. Since today the global black culture has been understood through the metaphor of the “Black Atlantic”, which represents an area of transnational exchange that connects all subjects of the black diaspora, I assume this same metaphor as a starting point for my reflection. However, I am interested in reflecting on one aspect of the Black Atlantic, which is its organizational dimension. If through the Black Atlantic is circulating today a set of contents that are shared by the black community worldwide, such as ideas and practices that are related to religion, music, literature and forms of organization, then we can say that the organization of Brazilian black movement also feeds itself from these multiple dimensions. To develop this argument, the thesis uses the case of the Brazilian black movement to analyze the diffusion process of a racialist transnational frame that is appropriate by the black movement as a basis for making a diagnosis, prognosis and resonance of actions to combat racism in Brazil, and for the establishment of structures for mobilization and action strategies of the movement. However, this appropriation does not occur without problems, because this frame faces other local frames, on a non-racialist character, which causes severe restrictions to transnational activism, once the black movement itself faces a dilemma between maintaining alignment with the transnational frame and seize political opportunities offered by racialism; or relativize this frame making some concessions in their proposals and their organization, in order to adapt to local frames, trading opportunities from these existing restrictions. To understand this dynamic, I propose the metaphor of the “Encounter of Waters” from the Amazon, as a point of argument complementary to the Black Atlantic, since it takes into account the local aspects of anti-racist struggle relying on miscegenation as autonomous identity that does not easily dilutes in the black identity. Besides developing these points, the thesis contributes to better understand the dialectic between global and local, as well as the tensions arising from frames in dispute. === Meu objetivo nesta tese é compreender o processo de transnacionalização do movimento negro brasileiro e as suas consequências para a luta antirracista no Brasil. Em outras palavras, busco compreender como os negros brasileiros se articulam com os negros do mundo para cumprir seus objetivos. Uma vez que hoje a cultura negra global tem sido compreendida a partir da metáfora do “Atlântico Negro”, que representa um espaço de trocas transnacional que conecta todos os sujeitos da diáspora negra, assumo esta mesma metáfora como ponto de partida para minha reflexão. Entretanto, me interessa refletir sob um dos aspectos do Atlântico Negro, que é a sua dimensão organizacional. Se é pelo Atlântico Negro que hoje circulam um conjunto de conteúdos que são compartilhados pela comunidade negra mundial, tais como idéias e práticas que estão relacionadas a religião, a música, a literatura e as formas de organização, então podemos afirmar que a organização do movimento negro brasileiro se alimenta também destas múltiplas dimensões. Para desenvolver esta linha de argumentação, a tese utiliza o caso do movimento negro brasileiro para analisar o processo de difusão de um frame transnacional racialista que é apropriado pelo movimento negro como base para a elaboração de um diagnóstico, prognóstico e ressonância das ações de combate ao racismo no Brasil e para a definição das estruturas de mobilização e das estratégias de ação do movimento. Contudo, esta apropriação não ocorre sem problemas, pois este frame enfrenta outros frames locais, de caráter não-racialista, o que acarreta severas restrições ao ativismo transnacional na medida em que o próprio movimento negro se vê diante do dilema entre manter o alinhamento com o frame transnacional e aproveita as oportunidades políticas oferecidas pelo racialismo, ou relativiza este frame fazendo algumas concessões em suas propostas e na sua organização, a fim de se adaptar aos frames locais, negociando estas oportunidades a partir das restrições existentes. Para entender esta dinâmica, proponho a metáfora do “Encontro das Águas” amazonense, como um ponto de argumentação complementar ao Atlântico Negro, pois leva em conta os aspectos locais da luta antirracista que se apoiam na mestiçagem como identidade autônoma que não se dilui facilmente na identidade negra. Além de desenvolver estes pontos, a tese contribui para compreender melhor a dialética entre o global e local, bem como as tensões advindas dos frames em disputa.